A STUDY OF EMOTIONAL INTELLIGENCE OF URBAN AND RURAL STUDENTS OF GRADUATE LEVEL - Kumari, Chanchal; Saxena, Deepshikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotional intelligence plays an important role in personal, social and academic life. Which directly and indirectly affects the behavior of the person. The purpose of the present study is to study the effect of geography on emotional intelligence of urban and rural students. For which 200 undergraduate students studying in colleges affiliated to Bundelkhand University, including 100 urban areas (50 male and 50 female) and 100 rural area (50 male and 50 female) have been taken. Dr. for data collection. Arun Kumar Singh and Dr. Emotional intelligence scale developed by Shruti Narayan has been used and the data was analyzed using mean, standard deviation and t-test. The conclusion of the research found that there is a significant difference in the emotional intelligence of urban and rural students. No significant difference was found between urban and rural girl students while significant difference was observed between rural and urban students. The findings of this research show that students’ emotional intelligence is influenced by their social and educational environment, so there is a need for teachers, parents, policy makers and mental health experts to develop effective strategies that help students develop their emotional competence and competence.